802 Lymphatic dysfunction in lupus contributes to cutaneous photosensitivity and lymph node B cell responses. (14th December 2022) - Ambler, William G; Howlander, Mir; Chalasani, Madhavi Latha S; Seltzer, Ethan S; Sim, JiHyun; Shin, Jinyeon; Schwartz, Noa; Dasoveanu, Dragos; Carballo, Camila B; Sevim, Ecem; Siddique, Salma; Rodeo, Scott; et al.
Abstract : Patients with systemic lupus erythematosus (SLE) are photosensitive, developing skin inflammation with even ambient ultraviolet radiation (UVR), and this cutaneous photosensitivity can be associated with UVR-induced flares of systemic disease, with increased autoantibodies and further end organ injury. Mechanistic insight into the link between skin disease and autoimmunity is limited. Signals from skin are transmitted directly to the immune system via lymphatic vessels, and here we show evidence for potentiation of UVR-induced lymphatic flow dysfunction in SLE patients and murine models. Improving lymphatic flow by manual lymphatic drainage (MLD) or with a transgenic model reduces both cutaneous photosensitivity and lymph node B cell responses. Mechanistically, improved flow restrains B cell responses by activating a fibroblastic reticular cell-monocyte axis. Our results point to a lymphatic flow- lymph node stromal axis as a link between photosensitivity and autoimmune responses and as a therapeutic target in lupus, have implications for understanding skin-immune interactions in other diseases such as skin cancer, and suggest the possibility of MLD as an immediately available, cost- effective adjunctive treatment in lupus and related diseases.